A chromosome-scale reference genome of Lobularia maritima, an ornamental plant with high stress tolerance. (1st December 2020) - Huang, Li; Ma, Yazhen; Jiang, Jiebei; Li, Ting; Yang, Wenjie; Zhang, Lei; Wu, Lei; Feng, Landi; Xi, Zhenxiang; Xu, Xiaoting; Liu, Jianquan; Hu, Quanjun
Abstract: Lobularia maritima (L.) Desv. is an ornamental plant cultivated across the world. It belongs to the family Brassicaceae and can tolerate dry, poor and contaminated habitats. Here, we present a chromosome-scale, high-quality genome assembly of L. maritima based on integrated approaches combining Illumina short reads and Hi–C chromosome conformation data. The genome was assembled into 12 pseudochromosomes with a 197.70 Mb length, and it includes 25, 813 protein-coding genes. Approximately 41.94% of the genome consists of repetitive sequences, with abundant long terminal repeat transposable elements. Comparative genomic analysis confirmed that L. maritima underwent a species-specific whole-genome duplication (WGD) event 22.99 million years ago. We identified 1900 species-specific genes, 25 expanded gene families, and 50 positively selected genes in L. maritima . Functional annotations of these genes indicated that they are mainly related to stress tolerance. These results provide new insights into the stress tolerance of L. maritima, and this genomic resource will be valuable for further genetic improvement of this important ornamental plant.